2018
DOI: 10.1007/s11695-018-3498-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Number of Ghrelin-Secreting Cells in the Gastric Fundus and Excess Weight Loss after Sleeve Gastrectomy

Abstract: There was a weak correlation between the total number of ghrelin-producing cells in the gastric fundus and plasma ghrelin levels with EWL after LSG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Lin et al 18 reported that complete resection of the gastric fundus may help in ghrelin suppression and prevent the increase in ghrelin levels after 6 months of the procedure. Another study 19 reported a strong positive correlation between plasma ghrelin levels and the total number of ghrelin-producing cells in the gastric fundus, which indicates that complete removal of the fundus would help reduce ghrelin levels in a substantial manner.…”
Section: Discussionmentioning
confidence: 97%
“…Lin et al 18 reported that complete resection of the gastric fundus may help in ghrelin suppression and prevent the increase in ghrelin levels after 6 months of the procedure. Another study 19 reported a strong positive correlation between plasma ghrelin levels and the total number of ghrelin-producing cells in the gastric fundus, which indicates that complete removal of the fundus would help reduce ghrelin levels in a substantial manner.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, another investigation discovered a robust positive correlation between plasma Ghrelin levels and the total number of Ghrelin-producing cells in the gastric fundus. This suggests that complete resection of the gastric fundus could effectively reduce Ghrelin levels [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recent work in humans has illustrated that the amount of stomach may be less important compared to the endocrine cells (ghrelin receptors) present in the stomach that is resected so histopathological studies are also necessary. 21 Traditional open partial gastrectomy is already performed in veterinary medicine for gastric necrosis associated with gastric dilatation volvulus and gastric neoplasia. [22][23][24][25] Complications encountered during these procedures include hemorrhage and leakage of gastric contents from subsequent dehiscence, but the true incidence is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As this technique appears safe in a live animal model future work is underway to determine the specific amount of stomach that must be removed in feline patients to generate weight loss. More recent work in humans has illustrated that the amount of stomach may be less important compared to the endocrine cells (ghrelin receptors) present in the stomach that is resected so histopathological studies are also necessary 21 …”
Section: Discussionmentioning
confidence: 99%